Drivers of general practice–type presentations to the emergency department in a remote outback community. (29th May 2021) - Fatima, Yaqoot; Hays, Richard; Knight, Sabina; Neilson, Anne; Fleming, Rhonda; Panaretto, Kathryn; Jatrana, Santosh; Skinner, Isabelle
Abstract: Objective: To estimate the number of general practice‐appropriate attendances in a remote emergency department and explore the reasons for patients' choice of service. Design: A four‐step case study approach was adopted, focusing on hospital emergency department (ED) attendances that were potentially manageable in general practice. Setting: A large, remote community with substantial populations of Indigenous peoples and fly‐in, fly‐out mining industry workers. The ED is experiencing rapid growth in demand for services for lower urgency. Participants: Patients attending the emergency department with lower urgency problems. Interventions: ED attendance data for 2016 were reviewed to identify lower urgency presentations. Patient records for 400 randomly selected presentations were subject to deeper analysis. A prospective survey was conducted over 6 months of 369 ED patients with lower urgency presentations. Main outcome measures: The proportion of patients attending the ED with GP‐appropriate problems and influences on their decisions to attend the ED. Results: About 48% of all attendances met the agreed definition of GP‐appropriate problems. About half of presentations were during the normal work hours and about half of patients stated that GP services were unavailable. Younger age, lack of information about local GP services, and perceptions of convenience contributed significantly to seeking ED care. Conclusion: Increasing the availability of GP services alone is unlikely to be sufficient to change service utilisation. Strategies should include raising community awareness of how and when to utilise the appropriate service, understanding different models of care, and the need to register with a general practice.